Who Bears the Risk? Mapping the Legal Liability of Artificial Intelligence Providers in Indonesia’s Regulatory Landscape - Ninik Zakiyah; Budi Santoso; Muh. Afif Mahfud; Edmon Makarim; Try Hardyanthi (Journal of Indonesian Legal Studies, 2026)
The accelerating advancement of Artificial Intelligence (AI) presents complex legal concerns in Indonesia, particularly in determining liability for damages arising from autonomous systems characterized by algorithmic opacity. Existing legal frameworks, including the Copyright Law, the Electronic Information and Transactions Law, and the Government Regulation on Electronic System Providers, have yet to adequately capture the legal implications of AI-based decision-making processes. This study employs a normative legal approach to examine Indonesia’s regulatory landscape and argues that AI cannot be acknowledged as a legal entity, thereby placing primary responsibility on AI system providers. While civil liability may be grounded in Articles 1365–1367 of the Civil Code, fault-based frameworks encounter significant challenges because of AI’s “black box” characteristics. Accordingly, this article proposes a shift toward risk-based approaches, including strict liability, shifting of the burden of proof, and mandatory transparency obligations. Furthermore, it emphasizes the need to transform ethical principles, as reflected in the Ministerial Circular on AI Ethics, into enforceable legal norms. A comprehensive regulatory framework integrating accountability, human rights, and legal certainty is therefore essential for responsible AI governance in Indonesia.